Reconstitution of nuclear protein export in isolated nuclear envelopes - Siebrasse, Jan Peter (The Rockefeller University Press, 2002)
Signal-dependent nuclear protein export was studied in perforated nuclei and isolated nuclear envelopes of Xenopus oocytes by optical single transporter recording. Manually isolated and purified oocyte nuclei were attached to isoporous filters and made permeable for macromolecules by perforation. Export of a recombinant protein (GG-NES) containing the nuclear export signal (NES) of the protein kinase A inhibitor through nuclear envelope patches spanning filter pores could be induced by the addition of GTP alone. Export continued against a concentration gradient, and was NES dependent and inhibited by leptomycin B and GTPγS, a nonhydrolyzable GTP analogue. Addition of recombinant RanBP3, a potential cofactor of CRM1-dependent export, did not promote GG-NES export at stoichiometric concentration but gradually inhibited export at higher concentrations. In isolated filter-attached nuclear envelopes, export of GG-NES was virtually abolished in the presence of GTP alone. However, a preformed export complex consisting of GG-NES, recombinant human CRM1, and RanGTP was rapidly exported. Unexpectedly, export was strongly reduced when the export complex contained RanGTPγS or RanG19V/Q69L-GTP, a GTPase-deficient Ran mutant. This paper shows that nuclear transport, previously studied in intact and permeabilized cells only, can be quantitatively analyzed in perforated nuclei and isolated nuclear envelopes.